2011
DOI: 10.4008/jcrpe.v1i2.35
|View full text |Cite
|
Sign up to set email alerts
|

Obesity in Children

Abstract: The prevalence of childhood obesity has increased dramatically during the past decades all over the world. The majority of obesity in adulthood has its origins in childhood which makes obesity a pediatric concern and the period when interventions should be done. Obesity is associated with increased morbidity and mortality in adult life and several adverse consequences in childhood like insulin resistance, type 2 diabetes, dyslipidemia, polycystic ovarian syndrome, pulmonary and orthopedic disorders and psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 42 publications
1
77
0
8
Order By: Relevance
“…1 Childhood obesity prevalence has increased by three to four folds globally within past few decades; the obesity epidemic has resulted due to sedentary life style and decline in physical activity. [2][3][4] Many countries are paying a heavy price for this in the form of chronic diseases, such as diabetes mellitus and hypertension, at a younger age and mounting expenditure on the treatment of complications of chronic diseases. 5 Pakistan stands among those countries which have the prevalence of obesity, among boys and girls, between 15% to 20 %.…”
Section: Introductionmentioning
confidence: 99%
“…1 Childhood obesity prevalence has increased by three to four folds globally within past few decades; the obesity epidemic has resulted due to sedentary life style and decline in physical activity. [2][3][4] Many countries are paying a heavy price for this in the form of chronic diseases, such as diabetes mellitus and hypertension, at a younger age and mounting expenditure on the treatment of complications of chronic diseases. 5 Pakistan stands among those countries which have the prevalence of obesity, among boys and girls, between 15% to 20 %.…”
Section: Introductionmentioning
confidence: 99%
“…Esta distribución de sobrepeso y obesidad en los escolares podría explicarse mejor si se conocieran a fondo sus estilos de vida, así como antecedentes familiares, de acuerdo con lo explicado por otros investigadores, donde existe mayor frecuencia de niños con obesidad cuando los padres también la presentan (8,39). La obesidad abdominal evidenciada por la CC en la muestra fue predominante en los varones (31,9 %), similar a lo reportado en escolares de secundaria por Ceballos et al (35), siguiendo el patrón donde normalmente la distribución de grasa en los hombres con obesidad es en forma de "manzana" (40).…”
Section: Discussionunclassified
“…This particular predictor of MetS, which encompassed a wide range of conditions, ie, from only 1 overweight parent to 2 obese parents, was detected in 80% of children with MetS, thus underscoring the importance of both the genetic predisposition derived from first-degree relatives and the environmental influence as expressed by familial dietary culture. This observation may have considerable implications inasmuch as it has been shown that adolescents' nutritional preferences and physical activity patterns are shaped early in childhood 41 and are largely influenced by parental practices and familial environment. 42 It is noteworthy that although characteristics of participants at 6 to 8 years of age were candidates for the multivariate model, none of them entered the model when the birth characteristics were included; this finding suggests that birth weight/head circumference and parental overweight/obesity are more important for MetS risk than children's weight at age 6 to 8 years in the population studied.…”
Section: Efstathiou Et Al Metabolic Syndrome In Adolescents 907mentioning
confidence: 99%
“…Prevention and management of MetS in adolescence could not be specific to the syndrome, per se, but rather should be focused on the underlying central disorder of overweight and abdominal obesity and considered as a matter that involves the entire family. 41 With regard to intervention, the prevention of excess weight gain in preadolescence (ie, between early childhood and adolescence) may be recommended on the basis of the above data. Furthermore, specially designed research is required to identify with appropriate methodology the critical period for subsequent MetS development, because this may be more important than having a predictive risk score.…”
Section: Efstathiou Et Al Metabolic Syndrome In Adolescents 907mentioning
confidence: 99%